Immunity, Community, Biopolitics - Roberto Esposito (Las Torres de Lucca, 2015)
This lecture was given on 19 October 2011, by Professor Roberto Esposito at the Faculty of Philosophy at the University Complutense of Madrid. It was one of the activities organized by the Graduate Students Association TALES in collaboration with the President of the Faculty.